Sejarah Awal Asal Usul Simalungun: Kajian Filologi - Cristien Oktaviani Saragih; Lastiur Sinaga; Doan Yohanes Manullang; Rido Silaban; Herlina Ginting (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to philologically examine the Simalungun script manuscript containing the early history of Simalungun. This manuscript is one of the important sources in understanding the history, culture, and identity of the Simalungun people from a traditional perspective. This study uses a philological approach by implementing several stages, namely inventory, physical description of the manuscript, transliteration into Latin letters, translation into Indonesian, and content analysis. Through this method, the content of the text can be revealed in depth to reconstruct historical information and cultural values contained in the manuscript scientifically. This research is important to do considering that the existence of Simalungun script manuscripts is increasingly rare and has not received much special scientific attention. The results of the analysis show that the manuscript contains a narrative about the origins of the Simalungun people, including the story of ancestral migration, the formation of clan areas, traditional leadership systems, and cultural values that are passed down from generation to generation. In addition to being a historical document, this manuscript also reflects the identity and outlook on life of the Simalungun people in the past. Through this philological study, the manuscript was successfully reconstructed and interpreted scientifically so that it can become an important source in preserving culture and strengthening regional script literacy.